Nucleophilic 18F-Fluorination of Anilines via N-Arylsydnone Intermediates - Narayanam, Maruthi Kumar; Ma, Gaoyuan; Champagne, Pier Alexandre; Houk, Kendall N.; Murphy, Jennifer M. (Synlett, 2018)
Preparation of [18F]fluoroarenes with nucleophilic [18F]fluoride for positron emission tomography (PET) molecular imaging research is a challenging chemical endeavor. Advances in radiofluorination have soared in the last decade, broadening the availability of potential [18F]fluoroarenes. In this Synpacts article, we highlight the recent development from our laboratory of a practical radiofluorination of anilines via N-arylsydnone intermediates to afford [18F]fluoroarenes. Further, we emphasize the utility of this methodology towards peptide labeling applications by preparing an 18F-labeled neuropeptide.1 Introduction2 Nucleophilic Radiofluorination of N-Arylsydnones3 Substrate Scope and Applications4 Conclusion
Keywords: fluorine-18; sydnone; bioorthogonal chemistry; fluoroarene; peptide labeling